2003
DOI: 10.1002/j.1939-4640.2003.tb02661.x
|View full text |Cite
|
Sign up to set email alerts
|

Balance of Apoptosis and Proliferation of Germ Cells Related to Spermatogenesis in Aged Men

Abstract: To clarify whether germ cell apoptosis is related to a decrease of germ cells in the aged testis with impaired spermatogenesis, we investigated the apoptotic rate of each germ cell type. Testicular specimens were obtained by orchiectomy from 36 men with advanced prostate cancer and by testicular biopsy from 21 men with obstructive azoospermia, which served as controls. The terminal deoxynucleotidyl transferase-mediated nick end labeling (TUNEL) technique was used to identify apoptosis. As a marker of cell prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 18 publications
2
64
2
Order By: Relevance
“…Previous reports demonstrated the association between advancing age and the expression of early apoptotic markers as evidenced by the significant increase in plasma membrane translocation of PS, as well as with a more subtle proportion of spermatozoa carrying DNA fragmentation (Moskovtsev et al, 2010;Wyrobek et al, 2006). Moreover, it has been shown that apoptosis increases with age, producing an accelerated germ cell loss (Kimura et al, 2003), related to the falling androgen levels and/or an increase in oxidative stress in the tissue (Samanta, Sahoo, & Chainy, 1999). …”
Section: Discussionmentioning
confidence: 98%
“…Previous reports demonstrated the association between advancing age and the expression of early apoptotic markers as evidenced by the significant increase in plasma membrane translocation of PS, as well as with a more subtle proportion of spermatozoa carrying DNA fragmentation (Moskovtsev et al, 2010;Wyrobek et al, 2006). Moreover, it has been shown that apoptosis increases with age, producing an accelerated germ cell loss (Kimura et al, 2003), related to the falling androgen levels and/or an increase in oxidative stress in the tissue (Samanta, Sahoo, & Chainy, 1999). …”
Section: Discussionmentioning
confidence: 98%
“…In spermatogonia of aged men, both expression of Ki-67, a marker of cell proliferation activity, and apoptotic rate were found to be decreased compared to young controls [92]. In contrast to spermatogonia, apoptotic rate of primary spermatocytes, as shown by TUNEL positivity, was significantly elevated compared to controls, which might, in part, explain the mechanism of germ cell loss in aged men [92]. The discrepancy might be due to an age-related deterioration of spermatogonial stem cell niche accompanied by a compensatory decrease in apoptotic spermatogonia [91].…”
Section: Free Radical Theory Of Aging and Apoptosismentioning
confidence: 89%
“…Although apoptosis is essential for spermatogenesis under normal conditions, the balance between proliferation of spermatogonia and apoptosis of different germ cell types appears to be disturbed with aging [91]. In spermatogonia of aged men, both expression of Ki-67, a marker of cell proliferation activity, and apoptotic rate were found to be decreased compared to young controls [92]. In contrast to spermatogonia, apoptotic rate of primary spermatocytes, as shown by TUNEL positivity, was significantly elevated compared to controls, which might, in part, explain the mechanism of germ cell loss in aged men [92].…”
Section: Free Radical Theory Of Aging and Apoptosismentioning
confidence: 99%
“…Nodera et al [2001] also reported the appearance of TUNEL positive cells after 3 w of zinc deficiency in testes and thymus of 7 w old Sprague Dawley rats. Abnormally accelerated apoptosis of germ cells may lead to an imbalance of cell proliferation and death resulting in spermatogenic impairment [Takagi et al 2001;Kimura et al 2003]. The correct balance between the apoptotic pathways is important for the maintenance of genomic integrity while preventing unnecessary cell death [Clarke and Allan 2009].…”
Section: Groupsmentioning
confidence: 99%